Nursing team stress in the perioperative period: an integrative review - Brandão, Dafne Eva Corrêa; Galvão, Cristina Maria (Rev Rene, 2013)
This integrative review aimed at analyzing evidences available in literature regarding stress levels in nursing teams during the perioperative period. Primary studies were searched in the following databases: PubMed, CINAHL and LILACS. Included studies were grouped into the following thematic categories: stress level in the workplace and stress factors (n=8) and stress coping strategies used by the nursing staff (n=6). Evidence suggests that stress in the workplace worsens the health of the nursing team, provoking undesirable effects both in the professional and personal lives of these professionals. The assessment of working conditions to identify the main stressing factors and the implementation of individual and organizational measures to reduce nursing teams stress may increase productivity and workers’ satisfaction, improving the assistance quality offered to surgical patients. DOI:https://doi.org/10.15253/2175-6783.20130004000021